Determination of geometric factor for crack growing from a notch (2023)
This manuscript studies the behavior of an ASTM A 36 structural steel specimen with a circular stress concentrator of variable diameter and a notch using computational modeling of finite elements (Ansys) and fracture mechanics, the test specimen has a thickness of 5 mm and a notch of 30 mm with opening of 45° was subjected to cyclic axial load and the diameter of the concentrator varies from 5mm, 9mm, 13mm, 17mm and 21 mm. This in order to establish the function that describes the behavior of the dimensionless geometrical factor (ß) in the calculation of the Stress Intensity Factor (SIF). For each selected diameter, the characteristic equation is obtained using the Support Vector Machine algorithm based on the Kernel equations. These results were compared with other accepted modes, obtaining a high degree of correlation and an error percentage close to 1.7%. As a main contribution, a new general mathematical model is obtained for specimens of defined geometry and concentrator of circular stress. © International Research Publication House